O ensino e aprendizagem da Língua Portuguesa como segunda língua para o aluno surdo: uma análise na escola E. E. F. E M. Cristo Trabalhador em Abaetetuba-PA - FERREIRA, Naylane da Costa (2021)
This research aims to know which pedagogical didactic procedures are used in the teaching of the Portuguese Language to deaf students, specifically, High School students at the State School of Elementary and Middle Christ Worker, located in Abaetetuba / PA. For this, we used the technical procedure called participant research. In which a research starts from the contact between researchers and members of the investigated situations. Data collection was through interview and observation. The research is organized into chapters, where the first deals with the educational history of the deaf; The second chapter brings innovations for the teaching of Portuguese to students such students; and finally, I report in the last chapter the methods currently used in teaching Portuguese.